ANALYTICAL STUDY OF OSIS MANAGEMENT IN FORMING STUDENT CHARACTER AT MTSS DARUL AMAN ACEH BESAR DISTRICT - Suzanni Suzanni (Journal of Higher Education and Academic Advancement, 2024)
MTs Darul Aman, Aceh Besar District is one of the schools or madrasas in Darussalam District which tries to shape student character, both through classroom learning and through the OSIS. The OSIS of MTs Darul Aman, Aceh Besar District, has many programs, but it requires the cooperation of good teachers and management to develop OSIS members so that they have good character. This research is qualitative in nature. Qualitative research is a research procedure with descriptive data results. In collecting data, researchers carried out observation, interviews and documentation studies. Observations were carried out by means of interviews and documentation studies. The interview guide used was in the form of open ended and probing questions . The documentation study in this research was carried out on various notes and documentation regarding profiles and backgrounds, data or documents related to OSIS management in shaping student character. OSIS planning in shaping student character. Every OSIS activity at MTs Darul Aman, Aceh Besar District, always begins with planning contained in the work program created by the OSIS management together with the guidance and guidance of the School Principal. The process is always carried out throughout the day. Because it is believed that a good process will produce what is expected to shape the student's character. Evaluations carried out by supervisory teachers help develop the management of the OSIS administrators. Starting from program planning to the evaluation process and helping to communicate funding sources for activities to the school principal. The student's character can be seen from every activity , does have a positive influence on students. Because for every activity, students are always given targets for change